(untitled) (World Bulletin of Management and Law, 2026)
The article examines the structural and functional characteristics of unicameral and bicameral parliaments, as well as analyses the representative nature of parliamentary activity. Special attention is given to the role of a member of parliament as a key actor of representative authority, which is of particular importance for post-Soviet states characterized by low levels of public trust in state institutions. Based on international comparative statistics, the ratio between population size and the number of parliamentarians is assessed, the causes of parliamentary overload are identified, and factors influencing the quality of representation are examined. The article discusses arguments in favor of increasing the number of seats in the lower chamber of the Parliament of Uzbekistan, including demographic trends, the need to strengthen the system of checks and balances, improving the efficiency of lawmaking, enhancing work within electoral districts, and expanding the participation of vulnerable population groups. Special attention is paid to international standards on seat reservation and the specifics of their application. The study concludes that a gradual expansion of parliamentary size and optimization of its structure is advisable in the long term to improve the quality of representation and the effectiveness of parliamentary governance.